Bauman and contemporary sociology a critical analysis - Rattansi, Ali (Manchester University Press, 2017)
This book offers an incisive and original perspective on the works of Zygmunt Bauman, perhaps the greatest sociologist of the late twentieth century. It examines the limitations of his approach while recognising the importance of his legacy as a theorist who insisted on the need for moral engagement.